2022
DOI: 10.1186/s12890-022-02153-1
|View full text |Cite
|
Sign up to set email alerts
|

Self-management behavior, associated factors and its relationship with social support and health literacy in patients with obstructive sleep apnea–hypopnea syndrome

Abstract: Background The proportion of patients with obstructive sleep apnea–hypopnea syndrome (OSAHS) is increasing year by year in China, which has become a major public health problem. Self-management of OSAHS and multiple support from caregivers are key to low hospital admissions and high quality of life for patients with OSAHS. Social support and health literacy are the main promoters of self-management behavior. However, their contributions have not been adequately studied. The purpose of this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Moreover, a previous study suggested that social support had a positive effect on health literacy, improving medication adherence among patients with hypertension [ 14 ]. This is because sufficient social support from families, friends, peers, colleagues, and healthcare professionals can help patients read and understand health information [ 26 ]. For example, individuals with MetS can have someone regularly reminding them to take medications and adopt healthy lifestyles and have someone take them to see a doctor if it is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a previous study suggested that social support had a positive effect on health literacy, improving medication adherence among patients with hypertension [ 14 ]. This is because sufficient social support from families, friends, peers, colleagues, and healthcare professionals can help patients read and understand health information [ 26 ]. For example, individuals with MetS can have someone regularly reminding them to take medications and adopt healthy lifestyles and have someone take them to see a doctor if it is necessary.…”
Section: Discussionmentioning
confidence: 99%